Pengaruh Metode Problem Based Learning terhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VIII SMP Negeri 3 Pagaran Tahun Pembelajaran 2023/2024 - Cas Widya Purba; Simion D. Harianja; Robinhot Sihombing; Haposan Silalahi; Sandy Ariawan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The research aims to determine the positive and significant influence of the Problem Based Learning Method on the learning activity of Christian Religious Education and Ethics students in grade VIII of SMP Negeri 3 Pagaran for the 2023/2024 Academic Year. The hypothesis in this study is that there is a positive and significant influence of the Problem Based Learning method on the learning activity of grade VIII students of SMP Negeri 3 Pagaran for the 2023/2024 Academic Year. This study uses a quantitative method with an inferential descriptive type, with a population of all grade VIII students of SMP Negeri 3 Pagaran totaling 176 people with a sample of 35 people. The data collected by a closed questionnaire was 45 items. The questionnaire trial was carried out to 30 students at SMP Negeri 3 Pagaran, and so on the questionnaire was valid and reliable. The results of the analysis of the value of rcal=0.486> rtable=0.334 and that tcal=3.655> ttable=2.042 show that there is a relationship between the Problem Based Learning method and the learning activity of grade VIII students of SMP Negeri 3 Pagaran Academic Year 2023/2024 and obtained a simple regression equation, namely Ŷ = 32.44=0.34X. The hypothesis test was obtained Fcal > Ftable, which was 12.96 > 1.62, then H0 was rejected and Ha was accepted. This study concluded that there was a positive and significant influence between the Problem Based Learning Method on the Learning Activity of Grade VIII Students of SMP Negeri 3 Pagaran for the 2023/2024 Academic Year of 23.61%.